Calculation of Accurate Meshing Backlash for Cycloidal-pin Wheel Drive in RV Reducer - Yang Jingzhao; Deng Xiaozhong; Li Tianxing; Wang Changlu; Wang Guofeng; Xing Chunrong (Jixie chuandong)
The meshing backlash of cycloidal-pin wheel drive in RV reducer is the key factor that affects the transmission performance. At present,the formula method is adopted mainly to calculate the initial meshing backlash of cycloidal-pin wheel. But there are some differences between the theoretical result and the actual value because the formula method did not consider the change of node position in the process of drive. Taking the distance between the profiles in the direction of the common normal as the accurate meshing backlash is proposed. The traditional initial meshing backlash calculation method is analyzed and the tooth contact model of cycloidal-pin wheel is established,then the accurate meshing backlash at any angle is obtained. A theoretical basis for calculating and analyzing the exact meshing backlash of cycloidal-pin wheel drive in RV reducer is provided.